Sosialisasi Peraturan Komisi Pemilihan Umum Nomor 9 Tahun 2022 - Sanjung, M. Lukman; Fahlevi, Reza (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2022)
In the implementation of general elections, the community has a very important role in organizing a democratic party in a country. Therefore, the community cannot be separated from elections because the community is the determinant and main factor in the success of an election. Political participation is a benchmark in the running of democracy in a country. The higher the level of political participation of citizens in a country will indicate the more democratic the country. An important form of political participation is the political participation of citizens in elections. This community service program aims to provide understanding related to the general election commission regulation No. 9 of 2022 and increase public participation in general elections, especially Metro City youth for the successful implementation of general elections or democratic parties in 2024. The method used in this service activity is the PAR (Participatory Action Research) method with stages of planning, implementation and evaluation. The results of this socialization activity show that youth organizations can understand well how community participation in the general election and election of governors and deputy governors, regents and deputy regents, and/or mayors and deputy mayors.